Less exposed, more vulnerable? Understanding the sexual victimization of women with disabilities under the lens of victimological theories - Chopin, Julien (International review of victimology, 2024)
This study aims to examine the sexual victimization process of individuals with disabilities using the interactional victimology theoretical framework. Specifically, we compare the victimological indicators of four different situations: victims were not disabled, victims were physically disabled, victims were psychologically disabled, and finally, victims were both physically and psychologically disabled. The sample used in this study consists of 1,077 cases of extrafamilial sexual assaults involving adult victims in France. Bivariate and multivariate analyses are performed to examine the differences between cases where victims were not disabled (n = 500), victims were physically disabled (n = 243), victims were psychologically disabled (n = 276), and victims were both physically and psychologically disabled (n = 58). Findings show that disability is a factor increasing the severity of sexual violence and that the type of disability affects the parameters of the victimization process. Moreover, results show that sexual victimization of persons with disabilities is more likely due to their vulnerability than to their exposure to risks. Both theoretical and practical implications related to the vulnerability concept are discussed.